Cultural heritage management in Africa : the heritage of the colonized : edited by George Okello Abungu and Webber Ndoro. - Abungu George Okello; Ndoro Webber (Routledge / Taylor & Francis Group, 2023)
"Cultural Heritage Management in Africa explores the diversity of Africa's cultural heritage by analysing how and why this heritage has been managed, and by considering the factors that continue to influence management strategies and systems throughout the African continent. Including contributions from prominent scholars and heritage professionals working across Africa, the volume presents critical, contemporary perspectives on the state of heritage in the area. Chapters analyse the practices that emanated from different colonial experiences and consider what impact these had - and continue to have - on the management of African heritage. It also critically examines the ideological influence of independence movements on the African continent's management and remembering of heritage, and considers whether there are any differences in heritage management between countries that experienced armed conflicts and those that did not. The volume will be the first to critically assess the state of heritage management now, at a time when vital conversations about the balance between heritage and development is ongoing and the actions of new players have begun to impact the management and practice of heritage in the region. Cultural Heritage Management in Africa will be essential reading for those engaged in the study of museums and heritage, development, archaeology, anthropology, history and African studies. It will also be of interest to heritage and museum professionals who wish to learn more about the decolonisation of heritage" Provided by publisher
Introduction: The heritage of the colonized / George Okello Abungu and Webber Ndoro Post-Colonial Archaeology in East Africa / Herman O. Kiriama Museums and Heritage in West Africa / El Hadji Malick Ndiaye, Hamady Bocoum, and Augustin Hall The Exhibition of the African in Post-colonial Africa: Example from Kenya / David Mbuthia and Purity Kiura Heritage Governance in Post- Colonial Africa / Thabo Manetsi Legal protection of African cultural heritage in the 21st century and beyond: a prognosis and futures perspective / Ancila Nhamo and Seke Katsamudanga The Trouble with Participation: Heritage Places, Politics and Communities in Africa / Albino Jopela 'Nothing about Us, Without Us': Heritage, Development and Communities in West Africa / Wazi Apoh & Victoria Ndidi Osuagwu Slave Trade, Slavery, and the Politics of Heritage Representation in Africa: Examples from Kenya and Mauritius / Patrick Abungu and Jean Francois Lafleur The Indian Ocean and the history of Indenture: The making of "new" nationals and nations / Satyendra Peerthum & Kiran Chuttoo Jankee Heritage Management practice in Ethiopia: Is it different? / Temesgen Burka and Tsehay Eshetie World Heritage and development: Is UNESCO a barrier or facilitator and do African opinions matter? / Ishanlosen Odiaua & Webber Ndoro The Intangible in World Heritage in Africa: Recognizing the invisible: Case studies of the Mosi-oa-Tunya/Victoria Falls World Heritage ZAMBIA, Pendjari National Park, BENIN and Matobo Hill World Heritage Zimbabwe. / John Zulu and Hermionen. Boko Koudakossi Liberation heritage typology and World Heritage: From local dimensions to "universalism" / Pascall Taruvinga & Ziva Domingos The Nature-Culture divide in heritage Classification and Management in Africa: reality or a convenience of management / Musawa Musonda-Hamusonde and George Okello Abungu Colonial statues in post-colonial Africa: decolonizing the narrative or destroying the heritage? / Shadreck Chirikure, Webber Ndoro, Simbarashe S Chitima, Genius Tevera, Thomas Thondhlana World Heritage and Education in Africa: A landscape of shifting priorities / Sibongile Masuku and Soul Shava Conclusion
Includes bibliography and index
Keywords: Cultural property -- Africa -- Management; Cultural property -- Protection -- Africa; Historic preservation -- Africa; Cultural property -- Repatriation -- Africa